2018
DOI: 10.1016/j.archoralbio.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the T-box transcription factor gene, Tbx1, in mice induces differential expression of genes associated with cleft palate in humans

Abstract: Our findings demonstrate that TBX1 maintains normal growth and development of palatal shelves, mediated through the regulation of genes involved in muscle cell differentiation, nervous system development, and biomineral tissue development. Multiple factors in Tbx1-knockout mice may lead to various subtypes of cleft palate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Expression of Pax9 , whose mutations lead to cleft palate and tooth agenesis [ 70 ], is downregulated in the palatal shelves and pharyngeal region of Tbx1 -null embryos [ 34 , 71 ]. In Tbx1 -null palatal shelves, muscle- and bone-related genes are downregulated, whereas neuron- and collagen biosynthesis-related genes are upregulated [ 72 ].…”
Section: Craniofacial Phenotypes Of Dgs/vcfs Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of Pax9 , whose mutations lead to cleft palate and tooth agenesis [ 70 ], is downregulated in the palatal shelves and pharyngeal region of Tbx1 -null embryos [ 34 , 71 ]. In Tbx1 -null palatal shelves, muscle- and bone-related genes are downregulated, whereas neuron- and collagen biosynthesis-related genes are upregulated [ 72 ].…”
Section: Craniofacial Phenotypes Of Dgs/vcfs Mouse Modelsmentioning
confidence: 99%
“…In Tbx1 -null and Tbx1 flox/- ; Mesp1 - Cre embryos, the masseter, pterygoid, and temporalis muscles are intermittently absent [ 78 , 79 ]. Accordingly, muscle-related genes are also downregulated in Tbx1 -null palatal shelves [ 72 ]. Tbx1 acts upstream of critical transcription factors to form branchiomeric muscles.…”
Section: Craniofacial Phenotypes Of Dgs/vcfs Mouse Modelsmentioning
confidence: 99%
“…Mutations in the EYA transcriptional coactivator and phosphatase 4 (Eya4) and Fbxo11, which cause delayed or failed mesenchyme regression during ME cavitation, have also been associated with OM (Depreux et al, 2008;Del-Pozo et al, 2019a). T-box transcription factor 1 (Tbx1) deficiency disrupts the function of the muscles that control ET function (Fuchs et al, 2015;Funato and Yanagisawa, 2018), while OM model mice carrying mutations in the cell adhesion protein Cdh11 display ME cavitation defects (Kiyama et al, 2018). Further study of many of previous identified genes in mouse models is needed to elucidate the cellular and molecular mechanism of these genes in OM.…”
Section: Genes Involved In Anti-inflammatory Responses In Ommentioning
confidence: 99%
“…Among these genes, additional myosin family members are included (MYH15, MYH2, MYH3, MYH4, MYO18B, MYO15A). In Tbx1-knockout palatal shelves, a gene profile analysis showed that myosin heavy chain 3 (Myh3) and nebulin (Neb) were downregulated [31]. Other genes included in the GO:0008092 list have been related in some way to the OFC onset.…”
mentioning
confidence: 99%